Obesity, type 2 diabetes and hormone replacement therapy vs. colorectal tumors in the elderly - Szamocka, Małgorzata; Ameryk, Monika Anna; Meder, Agnieszka; Sokup, Alina; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Aims. A prophylaxis program for the early detection of colorectal cancer carried out by our department since the year 2000 has been extended to include people aged 65 and older. The subjects were asked additional questions regarding their dietary habits and possible coexistence of type 2 diabetes, and women were asked about the use of hormone replacement therapy. A physical examination, including measurements of nutritional status, was conducted. The aim of the study was to assess the effect of overweight, obesity, type 2 diabetes and hormone replacement therapy on the incidence of cancers and adenomas detected by colonoscopy screening in people aged 65 and older. Methods. The study method was standard colonoscopy screening conducted in people aged 65 and older, in whom no clinical signs suggesting the presence of colorectal cancer were observed. The subjects examined provided their answers to a number of questions related to coexisting conditions and medicines taken, and women were asked about their use of hormone replacement therapy in the past. Every subject underwent a thorough physical examination that included basic anthropometric measurements. Results. Subjects with obesity, type 2 diabetes, and women who had used hormone replacement therapy had a greater risk of developing colorectal cancer. Conclusions. The increased risk of colorectal cancer in people with obesity and type 2 diabetes, as well as women undergoing hormone replacement therapy, may be associated with insulin-like growth factor 1 (IGF-1). This polypeptide shows a similarity to insulin, is an active compound in the process of carcinogenesis and plays a role in the regulation of cell growth, proliferation, differentiation and apoptosis. Elucidating the molecular mechanism of action of IGF-1 is important for identifying the causes of tumorigenesis and can also be of significance for the future development of effective methods of treating malignancies.